Profesor Turun Padang Cultivating Environmental English Literacy with School Pupils of the Orang Asli Community - Hafizoah, Kassim; Fatimah, Ali; Nur Syafawati, Sabuan; Rosjuliana Hidayu, Rosli; Mohd Shafeirul Zaman, Abd Majid (UMPSA, 2024)
KUALA LIPIS, 3 December 2023 – The Orang Asli (OA) community in Malaysia constitutes about 1% of the total population, and in Pahang, the OA community is the largest in Peninsular Malaysia.